Discovery of Leishmania Druggable Serine Proteases by Activity-Based Protein Profiling - Porta, Exequiel O. J.; Isern, Jaime A.; Kalesh, Karunakaran; Steel, Patrick G. (Frontiers in Pharmacology, 2022)
Leishmaniasis are a group of diseases caused by parasitic protozoa of the genus Leishmania. Current treatments are limited by difficult administration, high cost, poor efficacy, toxicity, and growing resistance. New agents, with new mechanisms of action, are urgently needed to treat the disease. Although extensively studied in other organisms, serine proteases (SPs) have not been widely explored as antileishmanial drug targets. Herein, we report for the first time an activity-based protein profiling (ABPP) strategy to investigate new therapeutic targets within the SPs of the Leishmania parasites. Active-site directed fluorophosphonate probes (rhodamine and biotin-conjugated) were used for the detection and identification of active Leishmania serine hydrolases (SHs). Significant differences were observed in the SHs expression levels throughout the Leishmania life cycle and between different Leishmania species. Using iTRAQ-labelling-based quantitative proteomic mass spectrometry, we identified two targetable SPs in Leishmania mexicana: carboxypeptidase LmxM.18.0450 and prolyl oligopeptidase LmxM.36.6750. Druggability was ascertained by selective inhibition using the commercial serine protease inhibitors chymostatin, lactacystin and ZPP, which represent templates for future anti-leishmanial drug discovery programs. Collectively, the use of ABPP method complements existing genetic methods for target identification and validation in Leishmania.